Understanding Student Perspectives on ICT Implementation in a Public School in Batam City - Zaki, Leil Badrah; Balqish, Nurhayati; Tambunan, Irwan Palar Hasudungan; Anisa, Qkhoirin; Pratiwi, Theodesia Lady (Program Studi Tadris Bahasa Inggris, Fakultas Tarbiyah, IAIN Kediri, 2024)
This research investigates the integration of Information and Communication Technology (ICT) into 21st-century English language learning, with a focus on understanding student perceptions and expectations. Conducted in collaboration with a public high school in Batam City, the study aims to explore teachers' perspectives on ICT in English Language Teaching (ELT), identify student needs for technology-based instructional materials, and propose strategies to enhance digital literacy for English learners. Through classroom observations and student surveys, the study reveals a generally positive attitude towards English learning and ICT integration among students, alongside areas for improvement in enhancing collaborative learning experiences. Despite teachers' readiness to implement e-learning, there's a perceived lack of sufficient ICT support in EFL classes. Interviews with Grade 11 students underscore the efficacy and enjoyment of online resources, with a desire for more innovative technology-based learning methods. Collaboration with University International Batam offers potential for implementing such methods, though logistical challenges remain. The findings reveal the importance of addressing gaps in ICT integration to optimize English language learning experiences for students.